2009
DOI: 10.1590/s1679-62252009000100013
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress biomarkers and aggressive behavior in fish exposed to aquatic cadmium contamination

Abstract: The objective of this study was to investigate the possible link between cadmium exposure, hepatic markers of oxidative stress and aggressive behavior in Nile tilapia (Oreochromis niloticus). Fish were first exposed to 0.75 mg/L CdCl 2 for 15 days (12 isolated fish for each group) and afterward a behavioral test was performed. Fish from the control and cadmium-exposed groups were paired for 1 h (6 pairs of fish per group) for determination of aggressiveness parameters. Immediately after the behavioral test, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 50 publications
3
26
0
Order By: Relevance
“…Rammal et al (2010) reported a positive correlation as a statistically significant between oxidative stress and aggressive behavior in male adult rats. Almeida et al (2009) investigated the relationship between oxidative stress and liver markers after cadmium exposure in order to evaluate aggressive behavior in the Nile tilapia (Oreochromis niloticus). In cats exposed to cadmium, the decrease and decrease in aggression behaviors were reflected in glutathione peroxidase (GSHPx) levels.…”
Section: Discussionmentioning
confidence: 99%
“…Rammal et al (2010) reported a positive correlation as a statistically significant between oxidative stress and aggressive behavior in male adult rats. Almeida et al (2009) investigated the relationship between oxidative stress and liver markers after cadmium exposure in order to evaluate aggressive behavior in the Nile tilapia (Oreochromis niloticus). In cats exposed to cadmium, the decrease and decrease in aggression behaviors were reflected in glutathione peroxidase (GSHPx) levels.…”
Section: Discussionmentioning
confidence: 99%
“…In fish liver, agents reported to induce lipid peroxidation include cyanobacterial hepatotoxins, herbicides, and heavy metals (Almeida et al, 2009;Mela et al, 2013). However, data are limited concerning lipid peroxidation in fish liver following exposure to cyanobacterial neurotoxins or PSPs.…”
Section: Oxidative Stress and Lipid Peroxidationmentioning
confidence: 99%
“…SOD catalyzes the conversion of superoxide anion to H 2 O 2 , a precursor to the highly reactive OH -radical (Almeida et al, 2009). Previous studies demonstrated that toxicants such as microcystin, insecticides, chemical dyes, and heavy metals upregulate SOD levels in fish liver (Xu et al, 2009;Jin et al, 2010), but few studies have addressed hepatic SOD level in fish exposed to cyanobacterial neurotoxins or PSPs (Gavrilović et al, 2014).…”
Section: Sod Responsementioning
confidence: 99%
“…Cadmium (Cd), a heavy metal commonly found in the environment, has highly toxic effects, even at low concentrations [1]. Open dumping waste management landfill methods provide a source of anthropogenically produced Cd.…”
Section: Introductionmentioning
confidence: 99%